Platinum Nanoparticles Loaded on Activated Carbon as Novel Adsorbent for the Removal of Congo Red - M. Ghaedi; S. J. Hossaini; S. Ramezani (E-Journal of Chemistry)
Platinum nanoparticles loaded on activated carbon as novel adsorbent was successfully applied for efficient removal of congo red. The influences of effective parameters including contact time, pH and temperature, amount of adsorbents and concentration of initial dye on the efficiency of removal of congo red from aqueous solution were investigated. Adsorption experiments indicate that the extent of adsorption is strongly dependent on pH of solution. Thermodynamic parameters like Free energy of adsorption, enthalpy and entropy changes were calculated to know the nature of adsorption. The calculated values of free energy of adsorption (negative value) indicate that the adsorption process is spontaneous. The estimated values of enthalpy and entropy both show the positive sign, which indicate that the adsorption process is endothermic and the dye molecules are organized on the adsorbent surface in more randomly fashion than in solution. Fitting experimental data to different kinetic models including first order, pseudo second order and Elovich and intra-particle diffusion models shows that the rate of dye adsorption follows pseudo second order model and involvement of intera- particle diffusion mechanism.